Role of Vitamin D in Near Sightedness: Doi: 10.36351/pjo.v36i2.990 - Malik, Yasir Iqbal; Malik, Aqsa; Shabbir, Rabbia; Zaman, Atteaya; Talib, Masooma (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the levels of Vitamin D in children with myopia and to compare them with age matched controls. Study Design: Case control study. Place and Duration of Study: The study was conducted in Naseer Memorial Hospital, Dadhyal Azad Kashmir from March 2016 to March 2017. Material and Methods: Two hundred patients were selected using convenient sampling technique and were divided two groups (group I Myopic and group II control). Myopia was labeled if after subjective refraction a Spherical Equivalent (SE) of ?0.50 diopters (D) or more was found. Vitamin D levels were measured by radioimmunoassay technique with Diasorin SR® kit following the user’s manual. Vitamin D levels less than 20 ng/ml were considered Vitamin D deficient following the standards of American academy of pediatrics. The collected data was entered in the statistical package for social sciences (SPSS) version 21 for analysis. Independent t–test was used to determine the significant difference of means between controls and patients. P-values less than 0.05 were considered significant. Results: Mean age of controls and myopes were 10.65 ± 3.9 and 10.20 ± 2.5 years respectively. Vitamin D levels in myopic children were found to be 14.95 ± 3.75 ng/ml and there was no significant difference in mean values of Vitamin D levels in myopic and control group. Conclusion: We found no difference in Vitamin D levels of myopic and non myopic children and concluded that Vitamin D has no role in development or progression of myopia.